2019
DOI: 10.1007/s12351-019-00508-x
|View full text |Cite
|
Sign up to set email alerts
|

Assigning a house for refugees: an application of a multiple criteria nominal classification method

Abstract: This paper proposes the use of a Multiple Criteria Decision Aiding (MCDA) nominal classification method to tackle a dramatic current social problem: the accommodation system for refugees. In recent years, the number of people in need of protection and assistance as a consequence of forced displacement has drastically increased. As many other European cities, Turin (Italy) offers to refugees temporary places for a limited time span, but they are insufficient and often inadequate. Meanwhile, there are several un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Meanwhile, Sierra et al [39] reported several examples of multi-criteria methods, including social aspects. Given that the urban environment is a multidimensional system, projects must pay attention to different points of social and environmental views to make sustainable cities and architectures; consequently, multi-criteria evaluation is a useful framework to address them [40]. Due to increasing social inequalities, the formation of class distinctions and crime issues in the society, a growing interest in social aspects of communities can be observed.…”
Section: The 2030 Agenda and Sustainabilitymentioning
confidence: 99%
“…Meanwhile, Sierra et al [39] reported several examples of multi-criteria methods, including social aspects. Given that the urban environment is a multidimensional system, projects must pay attention to different points of social and environmental views to make sustainable cities and architectures; consequently, multi-criteria evaluation is a useful framework to address them [40]. Due to increasing social inequalities, the formation of class distinctions and crime issues in the society, a growing interest in social aspects of communities can be observed.…”
Section: The 2030 Agenda and Sustainabilitymentioning
confidence: 99%
“…In this context, also the use of multi-criteria methodological frameworks for assessing social sustainability started gaining attention in recent decades; for example [25] proposed the concept of social multi-criteria evaluation as a useful framework for the application of social choices to difficult and complex contemporary problems and [26] reported numerous examples of multi-criteria methods including social aspects. Since the urban environment is a multidimensional system, projects need to consider different points of view in order to create sustainable cities and architectures, and therefore, multi-criteria evaluation is an appropriate framework to address them [27].…”
Section: Introductionmentioning
confidence: 99%